Fear, Heterodoxy, and Crime in Traditional China - Previato, Tommaso, (Asian Studies E-Books Online, Collection 2024., 2024)
This multi-contributor volume examines the evolving relationship between fear, heterodoxy and crime in traditional China. It throws light on how these three variously interwoven elements shaped local policies and people's perceptions of the religious, ethnic, and cultural "other." Authors depart from the assumption that "otherness" is constructed, stereotyped and formalized within the moral, political and legal institutions of Chinese society. The capacity of their findings to address questions about the emotional dimension of mass mobilization, the socio-political implications of heterodoxy, and attributions of crime is the result of integrating multiple sources of knowledge from history, religious studies and social science. Contributors are Ágnes Birtalan, Ayumu Doi, Fabian Graham, Hung Tak Wai, Jing Li, Hang Lin, Tommaso Previato, and Noriko Unno.